2002
DOI: 10.1139/f02-019
|View full text |Cite
|
Sign up to set email alerts
|

Does red alder (Alnus rubra) in upland riparian forests elevate macroinvertebrate and detritus export from headwater streams to downstream habitats in southeastern Alaska?

Abstract: We assessed the influence of riparian forest canopy type on macroinvertebrate and detritus export from headwater streams to downstream habitats in the Tongass National Forest, southeastern Alaska. Twenty-four fishless headwater streams were sampled monthly, from April to August 1998, across four riparian canopy types: old growth, clearcut, young-growth alder, and young-growth conifer. Young-growth alder sites exported significantly greater count (mean = 9.4 individuals·m–3 water, standard error (SE) = 3.7) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 27 publications
2
57
0
Order By: Relevance
“…For instance, Swain et al (2014) showed a positive relation of invertebrate, algae, and sculpin densities along a gradient of long-term escapement numbers of spawning sockeye salmon (Oncorhynchus nerka) in central British Columbia. Wipfli and Musslewhite (2004) and Piccolo and Wipfli (2002) demonstrated higher rates of invertebrate subsidies from upland forested streams to downstream habitats as riparian alder increased in coastal Alaska. Similarly, reductions in subsidy inputs can have negative consequences for recipient ecosystems.…”
Section: Consumer Responses To Natural Variation In Subsidy Input Ratesmentioning
confidence: 99%
“…For instance, Swain et al (2014) showed a positive relation of invertebrate, algae, and sculpin densities along a gradient of long-term escapement numbers of spawning sockeye salmon (Oncorhynchus nerka) in central British Columbia. Wipfli and Musslewhite (2004) and Piccolo and Wipfli (2002) demonstrated higher rates of invertebrate subsidies from upland forested streams to downstream habitats as riparian alder increased in coastal Alaska. Similarly, reductions in subsidy inputs can have negative consequences for recipient ecosystems.…”
Section: Consumer Responses To Natural Variation In Subsidy Input Ratesmentioning
confidence: 99%
“…These effects could lead to changes in aquatic productivity and terrestrial invertebrate inputs to streams [117]. Some riparian tree species contribute more terrestrial invertebrate mass to streams than others [118] and red alder appears to support relatively high levels of prey for fish [117,119,120]. This is significant because over half of the prey biomass ingested by juvenile salmonids in southeastern Alaska is terrestrial and originates from adjacent riparian vegetation [117].…”
Section: Aquatic and Riparian Habitat Of Alder-conifer Standsmentioning
confidence: 99%
“…While conifer-derived LWD plays an important structural role in aquatic systems (pool formation, sediment capture, cover for fish), smaller alder-derived woody debris and leaf litter increased invertebrate densities and diversity important as instream or downstream sources of food for fish [89]. An alder component in previously harvested fishless headwater stands may offset negative effects of timber harvest (such as sedimentation and loss of coarse woody debris) on downstream, salmonid-bearing food webs [119]. They found that young-growth alder sites exported significantly greater count and biomass of macroinvertebrates (70% were aquatic) than did young-growth conifer sites, translating up to four times more fish biomass in suitable downstream habitats [119].…”
Section: Role Of Red Alder In Aquatic and Riparian Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations